Rating and characterization of an organization's safety culture to improve performance. Issue 2 (1st February 2021) - Musonda, Innocent; Lusenga, Elizabeth; Okoro, Chioma
Abstract: Health and safety (H&S) performance improvement in construction organizations is unlikely if culture is not improved. Despite the acknowledgement that culture improvement results in better H&S performance or behavior, there is still no consensus on how to measure and improve H&S culture in an organization. The study therefore aimed to characterize and rate construction organizations' H&S culture using existing H&S culture models and to determine the level on the safety culture maturity model (SCMM) and its relationship with H&S behavior in the organizations. Empirical data were collected using questionnaires distributed in three provinces in South Africa. Data were analysed using descriptive and inferential statistical techniques, to output mean scores, standard deviation and Pearson's correlation values. The study revealed a strong correlation between an organization's leadership, involvement, procedures, commitment, communication and competence (LIP +3C) and the Safety Culture Maturity as well as behavior. These findings demonstrate that improving the level of factors characterized by the LIP +3C model would lead to improving H&S performance as evidenced on the SCMM model and the exhibited behavior in workers and management. Cultural progress and maturity can be tracked using the SCMM model.